The meet of locally connected group topologies - Dorene J. Fox (International Journal of Mathematics and Mathematical Sciences)
The collection of all group topologies on a given group is a complete lattice partially ordered by inclusion. The purpose of this paper is to develop a convenient method of defining the meet of an arbitrary collection of group topologies and demonstrate that the meet of a collection of locally connected group topologies is also locally connected.